Research on post-processing of casing parts based on coordinate system conversion - Lv, Kangjian; Liu, Xu; Meng, Qinglu; Hao, Xiaozhong (Journal of physics. Conference series, 2025)
As a typical rotary body part, the wall surface of the casing part is distributed with many features such as bosses, slots, and holes, and in the process of CNC programming, it is necessary to create local coordinate systems for different features to Simplify programming. However, the extensive use of local coordinate systems leads to complex calculations in the post-processing process of casing parts, which requires high requirements for process personnel. To this end, post-processing of casing parts based on coordinate system conversion was proposed: firstly, the kinematic modeling was carried out for a typical five-axis CNC machine tool and the translation and rotation angle were solved. Then, the motion conversion relationship between the local coordinate system and the machining coordinate system is studied and analyzed. On this basis, based on the UG secondary development technology, an automatic process decision-making post-processing module for casing parts was developed. Finally, the effectiveness of the post-processing module is verified on typical casing parts by VERICUT simulation.